Свидание вслепую: [роман] / Татьяна Алюшина - Алюшина Татьяна Александровна (Еще раз про любовь, 2017)
Экземпляры: (20190328) / Инвентарный номер: 50157 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6